The Casual Effect Competitive Advantage of Community Enterprise in Nan Province - Somsawat, Sorrawat (Journal of Humanities and Social Sciences Thonburi University, 2024)
The objectives of this research were 1) to study the level of opinions regarding entrepreneurship orientation, marketing orientation, innovativeness, and competitive advantage off community enterprises in Nan Province, and 2) to study the causal relationship between entrepreneurship orientation, marketing orientation, innovativeness and competitive advantage that affect toward competitive advantage of community enterprise in Nan Province. The study was conducted with 300 people. Data were collected using questionnaires employing stratified sampling and simple random sampling. Structural Equation Models were analyzed using statistical packages. The results showed that the level of opinions of respondents towards entrepreneurship orientation, marketing orientation, innovativeness and competitive advantage is overall at a high level. Causal relationships affecting the competitive advantage of community enterprises in Nan province revealed that the developed causal effects were consistent with empirical data = 86.974, df=67, =1.298, p-Value = 0.051, SRMR= 0.015, RMSEA= 0.032, GFI= 0.966, CFI= 0.996, NFI= 0.984 Entrepreneurship orientation has a direct influence on marketing orientation. And direct influence on innovativeness. Marketing orientation influences competitive advantage, and innovativeness has a direct influence on competitive advantage, with statistical significance of 0.001, respectively. Entrepreneurship orientation has a direct influence on competitive advantage statistically significant at 0.01.